Rancang Bangun Kotak Penyimpanan Dengan Akses Masuk Menggunakan Rfid Berbasis IOT (Internet Of Things) - affandi, mohammad misbakhul; Abidin, zainal (Universitas Nurul Jadid, 2023)
A strongbox is a place to store goods, usually used at home, tourist attractions, libraries, sports fields or other public places. The function of the cabinet as a storage area certainly has a high level of security, because valuables are stored in it. The security of a safe cabinet depends heavily on the strength of its door lock. To this day, traditional metal safety locks are still often used. In addition to looking old-fashioned, the use of such locks is also not effective for securing items in a safe or a storage area. Therefore, an innovation is needed that can increase the level of security of a safe or storage cabinet by using RFID entry access and covert to the internet (IoT). The stages of research in this thesis include, literature study, system design, hardware design and software design, System Integration and testing stages. Based on the results of tests that have been carried out both on hardware and software that has been made and see the purpose of the research, it can be concluded as follows: this equipment has been tested and can be used as a locker for storing goods that has a higher level of security compared to conventional locks and can be controlled and monitored with a semartphone.